2010
DOI: 10.1007/s12032-010-9628-7
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome induced by pamidronate

Abstract: Two patients developed nephrotic syndrome and progressive loss of renal function following treatment with i.v. pamidronate. Renal biopsy revealed collapsing focal segmental glomerulosclerosis (FSGS) in both the patients. In one patient, renal function recovered and the nephrotic syndrome disappeared after discontinuation of pamidronate. The second patient became dialysis dependent despite discontinuation of therapy. Nephrotic syndrome due to collapsing FSGS is a serious complication of treatment with bisphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…18 They have also been shown to protect against bone loss in the renal transplant recipients, 1,7,19,20 although a specific risk is the potential to exacerbate a baseline low-turnover adynamic state. 1,21,22…”
Section: Introductionmentioning
confidence: 99%
“…18 They have also been shown to protect against bone loss in the renal transplant recipients, 1,7,19,20 although a specific risk is the potential to exacerbate a baseline low-turnover adynamic state. 1,21,22…”
Section: Introductionmentioning
confidence: 99%
“…Patterns such as toxic acute tubular necrosis have occurred in some patients who use zoledronic acid [77,78]. Other case studies found that some patients treated with pamidronate developed nephrotic syndrome, which results in a poor prognosis if it develops alongside impaired renal function [79]. However, the likelihood of severe renal failure from BP use is low if the BP is administered with the correct dosing regimen [80].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…For example, pamidronate (an osteoclast inhibitor) can also cause proteinuria with a collapsing FSGS-like picture on kidney biopsy, which may or may not improve with withdrawal of the offending agent. 34 …”
Section: Focal Segmental Glomerulosclerosismentioning
confidence: 99%